2014
DOI: 10.1007/s10900-014-9952-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Perceptions of Cancer Risk, Neighborhood Environmental Risks, and Health Behaviors of Blacks

Abstract: Cancer risk perceptions and cancer worry are shaped by race/ethnicity, and social, economic, and environmental factors, which in turn shape health decision-making. A paucity of studies has explored risk perceptions and worry in metropolitan areas with disparate environmental conditions and cancer outcomes. This study examined perceptions of cancer risk, neighborhood environmental health risks, and risk-reducing health behaviors among Blacks. A 59-item survey was administered to respondents in Metropolitan Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Age may play a role because a person's age is an indicator of how much experience he/she has with Pb contamination and whether they are likely to have young children [38,39]. Gender may influence behavior because women and children are more vulnerable to negative health outcomes from Pb exposure and might be more likely to practice health behaviors [40,41]. Affiliation with mining is likely relevant because several previous studies have linked involvement in livelihoods related to a polluting industry with lower perceived health risk [42,43].…”
Section: Hypothesesmentioning
confidence: 99%
“…Age may play a role because a person's age is an indicator of how much experience he/she has with Pb contamination and whether they are likely to have young children [38,39]. Gender may influence behavior because women and children are more vulnerable to negative health outcomes from Pb exposure and might be more likely to practice health behaviors [40,41]. Affiliation with mining is likely relevant because several previous studies have linked involvement in livelihoods related to a polluting industry with lower perceived health risk [42,43].…”
Section: Hypothesesmentioning
confidence: 99%
“…SC is a state where communities of color and low-income populations experience a greater burden of exposure to several pollution sources, including air toxics, due to the spatial distribution of pollution-emitting hazards (Burwell et al 2013; Rice L et al 2014a, b; Svendsen et al 2014; Wilson et al 2012a, b; Wilson et al 2013). In our present study, we assess the impact of sociodemographic factors on estimated cancer risk associated with air toxics in SC with a specific focus on comparing differences in cancer risk in urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could indirectly suggest that people consider pollution as a cause of cancer. Others studies had shown that people consider air and water pollution as a cause of cancer when they are questioned directly about these this association (Rice et al 2015, Peretti-Watel et al 2016. The reasons that only water pollution was related could be explained by the fact that water is scarce in the studied region and hence more valued.…”
Section: Discussionmentioning
confidence: 91%